Sistem Manajemen Kepegawaian dan Pencatatan Pekerja Migran Indonesia di BP3MI Riau dengan Metode Prototipe - MHD Anwar; Muhammad Ihsan Zul (Sekawan Institut, 2024)
Balai Pelayanan Pelindungan Pekerja Migran Indonesia (BP3MI) Riau, a government agency dedicated to protecting Indonesian migrant workers. The agency faces challenges with its unstructured and inefficient data management system. The use of Microsoft Excel for documenting the data of Indonesian Migrant Workers (PMI) and employees at BP3MI Riau is prone to data entry errors, time inefficiencies, unstructured data, potential damage, limited access, restricted analysis, difficulties in tracking changes, and a high risk of data loss. To address these issues, research was conducted to develop a more effective employee management and PMI data recording system using the prototype method. This method emphasizes user collaboration in understanding system requirements, resulting in practical solutions. The prototype method stages include user requirements gathering, designing input, process, and output needs, followed by rapid UML model design, program code implementation, and finally, testing. The system development results show that users have a very positive impression from the usability testing, achieving a score of 97.76%. This indicates the effectiveness of the prototype. The system significantly improves manual methods, enhancing the efficiency, accuracy, and accessibility of data at BP3MI Riau, and lays the foundation for future advancements with greater integration and automation prospects in BP3MI Riau's operations.